The complete part design handbook : for injection molding of thermoplastics - Campo, E. Alfredo (Hanser Publishers ; Hanser Gardner Publications, 2006)
This handbook was written for the injection molding product designer who has a limited knowledge of engineering polymers. It is a guide for the designer to decide which resin and design geometries to use for the design of plastic parts. It can also offer knowledgeable advice for resin and machine selection and processing parameters. Manufacturer and end user satisfaction is the ultimate goal. This book is an indispensable, all inclusive, reference guide. New illustrations, graphs and equations have been included to provide additional clarity for complex ideas.
Includes index.
Keywords: Injection molding of plastics -- Handbooks, manuals, etc.; Thermoplastics -- Design -- Handbooks, manuals, etc.; Plastics -- Handbooks, manuals, etc.; elektronické knihy; electronic books